2018
DOI: 10.1002/ajum.12114
|View full text |Cite
|
Sign up to set email alerts
|

Neonatologist performed point‐of‐care bowel ultrasound: Is the time right?

Abstract: Introduction: This review acquaints neonatal clinicians using point-of-care ultrasound with a range of pathological bowel ultrasound findings, with the aim to promote utility of this skill as a diagnostic assessment tool in diseased neonatal intestinal states. Overview: A range of normal and pathological bowel ultrasound findings are illustrated with case examples from our neonatal intensive care unit. The technical challenges of lack of familiarity with sonographic appearance of bowel (healthy and diseased), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…DS auscultation will have been a mainstream methodology for diagnosis of bowel condition in the foreseen future. Although point-of-care ultrasound can provide more detailed information on bowel peristalsis, bowel wall thickness and bowel vascularity [40], it can be only performed by medical professionals within hospital settings. By contrast, DS auscultation is much more convenient without imposing constraints on professional knowledge and geographical locations.…”
Section: Discussionmentioning
confidence: 99%
“…DS auscultation will have been a mainstream methodology for diagnosis of bowel condition in the foreseen future. Although point-of-care ultrasound can provide more detailed information on bowel peristalsis, bowel wall thickness and bowel vascularity [40], it can be only performed by medical professionals within hospital settings. By contrast, DS auscultation is much more convenient without imposing constraints on professional knowledge and geographical locations.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of standard "gut signature", peristalsis and normal vascularity are a sign of a healthy bowel and reassuring to the clinician. Point-of-care abdominal US in the diagnosis of NEC has shown a definitive utility in the hands of pediatric radiologists [14,15]. Our group is exploring the utility of neonatologist performed point-of-care abdominal US to exclude NEC from CPAP belly syndrome, and determine the real negative and positive predictive value of its utility.…”
Section: Diagnosis Of Cpap Belly Syndromementioning
confidence: 99%
“…22,23 Non-contracting bowel wall thickness varies by age but normally ranges between 1 and 2.6 mm. 23 Pathologically thickened bowels can show increased echogenicity and alteration of the normal layered 'gut signature'. Pathologically thinned bowel could reflect ischaemia or necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…23 Peristalsis is subjectively appreciable but could also be measured in a region of interest as movements per minute, with 10 or more considered normal. 23 Lastly, colour Doppler evaluation of mural blood flow is possible but is best characterised for NEC. Faingold et al 24 identified hyperaemia in early NEC with inflammation and an absence of Doppler signal in transmural ischaemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation